Advances in accounting behavioral research. Vol. 6 - Arnold, Vicky (Emerald, 2003)
This volume contains an eclectic collection of behavioral research papers that examine several very important issues. Several of the papers focus on various aspects of auditors' decisions such as professional commitment in public accounting firms, mitigating bias via group decision making, and appropriately using sample information to estimate errors in governmental auditing. The decisions of other professionals that use accounting information such as commercial lenders and divisional managers are also examined. Two papers examine how accounting information impacts the behaviors of individuals within an organization under various incentive structures. Two other papers provide perspectives on overall research with one developing a classification scheme for new assurance services and the other examining factors that impact research productivity of accounting faculty members.
Keywords: Accounting -- Psychological aspects -- Research.; elektronické knihy; electronic books